Impact of interest rate on commercial bank profitability in Malaysia / Nur Iylia Azira Mohd Isa - Mohd Isa, Nur Iylia Azira (Faculty of Business Management, 2017)
The main objective of this study is to examine the impact of interest rate on commercial bank profitability in Malaysia. From this study, there are three variables on commercial banks profitability. These variables namely net interest margin, fixed rate and interest on customer deposits. All these variables are called as independent variables. The dependent variable is return on assets. The data was analysed using panel data and this project paper had been tested for several statistics. The selected bank will be Affin Bank Berhad, CIMB Bank Berhad, HSBC Bank Malaysia Berhad, Malayan Banking Berhad, OCBC Bank (Malaysia) Berhad, Public Bank Berhad, United Overseas Bank (Malaysia) Bhd., and RHB Bank Berhad. These findings have proven that these three of independent variables are significant with dependent variable. This study also comes out several conclusion and recommendation for future research. From this research, we can say that when interest rate is increase, the net interest margin also will increase. Both of these factors are positive correlation with each other. Other than used net interest margin, fixed rate and interest on customer deposits, researcher also can used others factor such as net interest income, return on equity, loans and others. Some of the result will show the significant and normality, meanwhile for the others, might not show the significant.